2005
DOI: 10.1161/01.str.0000163083.59201.34
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Prevents Cerebral Infarction Via a Serotonergic 5-Hydroxytryptamine 1A Receptor–Dependent Mechanism

Abstract: Background and Purpose-Cannabidiol has been reported to be a neuroprotectant, but the neuroprotective mechanism of cannabidiol remains unclear. We studied the neuroprotective mechanism of cannabidiol in 4-hour middle cerebral artery (MCA) occlusion mice. Methods-Male MCA occluded mice were treated with cannabidiol, abnormal cannabidiol, anandamide, methanandamide, cannabidiol plus capsazepine, and cannabidiol plus WAY100135 before and 3 hours after MCA occlusion. The infarct size was determined after 24 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(157 citation statements)
references
References 26 publications
6
148
1
2
Order By: Relevance
“…Consistent with this hypothesis, the CB 1 /CB 2 agonist D 9 -tetrahydrocannabinol was shown to reduce cerebral infarction in a mouse model of MCAO by CB 1 receptor induced hypothermia (Hayakawa et al, 2004). Cannabidiol, the nonpsychoactive constituent of cannabis, also reduced cerebral infarction but this is thought to be due to increasing rCBF during ischemia via the serotonergic 5-hydroxytryptamine 1A receptor (Mishima et al, 2005). WIN55212-2, which stimulates both the CB 1 and CB 2 receptor, with greater affinity for the CB 2 receptors, has been shown to be neuroprotective in both global and focal models of ischemia.…”
Section: Discussionmentioning
confidence: 80%
“…Consistent with this hypothesis, the CB 1 /CB 2 agonist D 9 -tetrahydrocannabinol was shown to reduce cerebral infarction in a mouse model of MCAO by CB 1 receptor induced hypothermia (Hayakawa et al, 2004). Cannabidiol, the nonpsychoactive constituent of cannabis, also reduced cerebral infarction but this is thought to be due to increasing rCBF during ischemia via the serotonergic 5-hydroxytryptamine 1A receptor (Mishima et al, 2005). WIN55212-2, which stimulates both the CB 1 and CB 2 receptor, with greater affinity for the CB 2 receptors, has been shown to be neuroprotective in both global and focal models of ischemia.…”
Section: Discussionmentioning
confidence: 80%
“…In the case of TBI, damage is most commonly caused either by closed (concussion) or open head injury (stab wound). The cannabinoids having beneficial effects in these models included 1) dexanabinol (HU-211) [8][9][10][11], which is a synthetic compound having a chemical structure of a classic cannabinoid but no activity at cannabinoid receptors; 2) nonselective synthetic cannabinoid agonists such as HU-210, the active enantiomer of HU-211 [12], WIN 55,212-2 [13,14], TAK-937 [15,16], and BAY 38-7271 [17,18]; 3) phytocannabinoids such as Δ 9 -tetrahydrocannabinol (Δ 9 -THC) [19], which binds not only CB 1 R and CB 2 R, but also cannabidiol (CBD), which has no affinity at these receptors but was highly active against brain ischemia [20][21][22]; 4) endocannabinoids such as 2-arachidonoylglycerol (2-AG), in particular in TBI induced by closed head injury [23][24][25], but also in experimental ischemia [26], and also anandamide [27] and its related signaling lipids palmitoylethanolamide (PEA) [28], oleoylethanolamide [27], and N-arachidonoyl-L-serine (AraS) [29]; and 5) selective CB 2 R targeting ligands such as O-3853, O-1966, and JWH-133 [30][31][32][33][34][35]. Most of these studies were conducted with the cannabinoid administered at least after the cytotoxic insult [12-19, 21-26, 28-35].…”
Section: Cannabinoids and Acute Brain Damage: Stroke And Brain Traumamentioning
confidence: 99%
“…In addition, their strong anti-inflammatory profile appears to be one of the most consistent mechanisms leading to reduction of the lesion, by actions affecting resident, vascular, and peripheral cells. It is also important to remark that the benefits of certain cannabinoids in acute stroke and TBI also involve effects on other pharmacological targets, such as the blockade of NMDA receptors (e.g., HU-211 [8][9][10][11]), the activation of 5-HT 1A receptors (e.g., CBD [20][21][22]), and the activation of transient receptor potential vanilloid-type 1 receptors (e.g., PEA [36] and AraS) [29]). It is also possible that part of these beneficial effects may be related to the hypothermic effects of cannabinoids, but it is well known that such effects are CB 1 R-mediated [12,38,39].…”
Section: Cannabinoids and Acute Brain Damage: Stroke And Brain Traumamentioning
confidence: 99%
“…92 The same research group has verified that this effect was inhibited by WAY100135, a serotonin 5-hydroxytriptamine 1A (5-HT 1A ) receptor antagonist, but not by capsazepine, a vanilloid receptor antagonist, suggesting that the neuroprotective effect of CBD may be due to the increase in cerebral blood flow mediated by the serotonergic 5-HT 1A receptor. 93 Experimental evidence has suggested that beyond this action on the 5-HT 1A receptor, the protective effect of CBD on ischemic injury is also secondary to its anti-inflammatory action. 94 In another study, the same research group reported that, while repeated treatment with delta9-THC leads to the development of tolerance for this neuroprotective effect, this phenomenon is not observed with CBD.…”
Section: Action On Ischemiamentioning
confidence: 99%
“…In signal-transduction studies, CBD acts as an agonist at the human 5-HT 1A receptor. 119 This CBD action is probably involved in the protective effect of CBD on ischemia 93 and in its anxiolytic-like effects. 120 4.…”
Section: Anticancer Actionmentioning
confidence: 99%